1H-NMR Lipidomics, Comparing Fatty Acids and Lipids in Cow, Goat, Almond, Cashew, Soy, and Coconut Milk Using NMR and Mass Spectrometry - Brianna Williams; Shamika P. W. R. Hewage; Denzel Alexander; Harshica Fernando (Metabolites)
Background/Objectives: Lipids are an important component of human nutrition. Conventional milk is obtained from animals, and dairy milk is consumed by many people worldwide. Recently, milk consumers have been increasingly shifting towards plant-based milk options. The aim of the study was the qualitative identification of lipid metabolites in animal- and plant-based milk, the identification and comparison of the fatty acids (FAs) of milk, and the qualitative identification of the lipid groups among the milk varieties. Methods: Milk samples were obtained from local grocery stores. Lipids were extracted using a modified Folch method and analyzed using nuclear magnetic resonance (NMR) metabolomics. Gas and liquid chromatography mass spectrometry methods (GC-MS and LC-MS) were used to identify the FAs and lipid groups. Lipid weights were compared and the NMR profiles of the lipids analyzed by multivariate statistical analysis. Principal component analysis was performed for the milk lipids obtained from the animal, and plant milk varieties. Results: Clustering of NMR data showed two main clusters: cow/almond/cashew and goat/soy/coconut. GC-MS analysis of the methylated fatty acids (FAs) showed the presence of 12:0, 14:0, 16:0, 16:1, 17:0, 18:0, 18:1, 18:2, 20:1, and 20:2 in all milk types, while FAs 19:0 and 20:4 were observed only in the dairy milk. LC-MS data showed common masses that may indicate the presence of mono- and diacyl glycerols and several lysophospholipids among the different types of milk. Conclusions: This study shows the advantage of using NMR, GC-MS, and LC-MS to differentiate the lipids among different milk types and compare them on one platform.